Development of an Android-Based Cultural Heritage Map App - Luthfi, Muhammad Irfan; Wardani, Ratna; Septiyanti, Nisa Dwi (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
This study aims to (1) develop an Android-based cultural heritage map app that can provide the location of cultural heritages in the Special Region in Yogyakarta along with its descriptions, images, and videos; and (2) understand the quality of the app based on standard software quality testing ISO / IEC 25010 on functional suitability, performance efficiency, and compatibility. The development method utilized a waterfall software development model that consists of communication, planning, modeling, construction, and deployment. The results of this study are 1) an Android-based cultural heritage map app that can provide the location of cultural heritages in the Special Region of Yogyakarta along with its descriptions, pictures, and videos. and 2) the test results indicate the app meets the standards of ISO / IEC 25010 on the aspect of (1) functional suitability, entire functions of the app running 100%, (2) the compatibility of the app, compatible 100% of the co-existence, various operating systems, device types, and screen dimensions, (3) performance efficiency, the app successfully executed in 312 of the 321 test devices without any memory leak with the average of time behavior, CPU utilization, and memory utilization for Dalvik Virtual Machine are 0.022 seconds/thread, 10.71%, and 33.11 MB and the average of time behavior, CPU utilization, and memory utilization for Android Run Time are 0.020 seconds/thread, 9.9918%, and 154.582 MB.